2006
DOI: 10.1128/iai.74.2.961-967.2006
|View full text |Cite
|
Sign up to set email alerts
|

Ancylostoma caninum MTP-1, an Astacin-Like Metalloprotease Secreted by Infective Hookworm Larvae, Is Involved in Tissue Migration

Abstract: Infective larvae (L3) of nematodes secrete macromolecules that are critical to infection and establishment of the parasite in the host. The dog hookworm Ancylostoma caninum secretes an astacin-like metalloprotease, Ac-MTP-1, upon activation in vitro with host serum. Recombinant Ac-MTP-1 was expressed in the baculovirus/insect cell system as a secreted protein and was purified from culture medium by two separate methods, cation-exchange fast-performance liquid chromatography and gelatin-affinity chromatography.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
80
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 28 publications
4
80
0
1
Order By: Relevance
“…In particular, tissue-invading hookworm L3 release metalloproteases and ASPs. The function of the A. caninum metalloprotease-1, Ac-MTP-1, has recently been characterized by us (Williamson et al, 2006). We have shown that MTP-1 favors tissue penetration: anti-MTP-1 antiserum inhibited the ability of the recombinant protein to digest collagen by 85% and inhibited larval migration through tissue in vitro by 75% (Williamson et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In particular, tissue-invading hookworm L3 release metalloproteases and ASPs. The function of the A. caninum metalloprotease-1, Ac-MTP-1, has recently been characterized by us (Williamson et al, 2006). We have shown that MTP-1 favors tissue penetration: anti-MTP-1 antiserum inhibited the ability of the recombinant protein to digest collagen by 85% and inhibited larval migration through tissue in vitro by 75% (Williamson et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…The function of the A. caninum metalloprotease-1, Ac-MTP-1, has recently been characterized by us (Williamson et al, 2006). We have shown that MTP-1 favors tissue penetration: anti-MTP-1 antiserum inhibited the ability of the recombinant protein to digest collagen by 85% and inhibited larval migration through tissue in vitro by 75% (Williamson et al, 2006). Similarly, rat and dog antiserum against Na-ASP-2 was able to inhibit larval migration through tissue in an in vitro system Goud et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes in the arrested stage do not express sc-sp-1; however, this gene was overexpressed in recovered nematodes, particularly those in the gut lumen preparing to invade the insect hemocoelium. In other parasitic nematodes, the role for serine proteases in tissue invasion was inferred based on expression analysis (52)(53)(54). In vitro assays showed that, although the resistant stage does not express scsp-1, the nematodes initiate expression shortly after stimulation with insect tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Many of these parasites to complete their life cycle have to migrate or invade through various organs of their hosts. During this journey, expression and release of MMPs by various parasitic nematodes have been associated with the pathology resulting from histolysis (Williamson et al, 2006). Genetic analysis and cDNA cloning of MMPs have been evaluated in few parasitic nematodes (Salter et al, 2002;Uparanukraw et al, 2001;Wang et al, 2001).…”
Section: Introductionmentioning
confidence: 99%